The changing face of fractures of the hip in Northern Ireland: a 15-year review. (September 2017) - Tucker, A.; Donnelly, K. J.; McDonald, S.; Craig, J.; Foster, A. P.; Acton, J. D.
Abstract : Aims: We reviewed all patients who sustained a fracture of the hip and were treated in Northern Ireland over a period of 15 years to identify trends in incidence, the demographics of the patients, the rates of mortality, the configuration of the fracture and the choice of implant. Patients and Methods: Since 01 January 2001 data about every fracture of the hip sustained in an adult have been collected centrally in Northern Ireland. All adults with such a fracture between 2000 and 2015 were included in the study. Temporal changes in their demographics, the mode of treatment, and outcomes including mortality were analysed. Results: The incidence of fractures of the hip, in Northern Ireland, rose from 54 in 100 000 in 2000 to 86 in 100 000 in 2015. If these trends continue, we predict this rising to 128 in 100 000 in 2030. We found that these patients are becoming older and increasingly frail, as assessed by the American Association of Anesthesiology grade. Complex extracapsular fractures have become more common since 2009, which may explain the increased use of cephalomedullary nails. Despite increasing frailty, the 30-day and 12-month rates of mortality fell significantly (p = 0.002 and 0.001, respectively). Conclusion: Fractures of the hip are becoming more common and more complex in an aging, increasingly frail population. We expect these trends to continue. This will place an increasing economic and clinical strain on healthcare systems. Forward planning is essential to put systems in place that can deal with the increasing demand. Cite this article: Bone Joint J 2017;99-B:1223–31.